Generation Capacity Expansion Considering Hydrogen Power Plants and Energy Storage Systems - Hernan Gomez-Villarreal; Miguel Canas-Carreton; Rafael Zarate-Minano; Miguel Carrion (IEEE Access)
The design of decarbonized power systems is one of the most relevant and challenging problems that power system planners are facing nowadays. In this sense, the replacement of natural gas turbines by H2-fired gas turbines in future power systems may constitute a solution to reduce greenhouse gas emissions maintaining the dispatchability of the system. This work develops a novel generation capacity expansion formulation that considers the possibility of installing new H2-fired gas turbines, as well as renewable generation and different storage technologies. The proposed model also determines the investment decisions related to the installation of electrolyzers to produce H2, as well as H2 storage facilities. The provision of reserve capacity by generating units, storage and electrolyzers is also considered to determine the optimal investment decisions. The uncertainty related to the demand growth and the capital costs of electrolyzers and H2 storage is explicitly considered by using a stochastic programming formulation. A realistic case study based on an actual isolated power system is solved to test the proposed formulation. The obtained results indicate that H2 power plants are installed in all cases in which this technology is available. Additionally, the capacity installed of electrolyzers is over 2.5 times higher than that of H2 power units.